Political Rights of the Citizen in the 2014 Election and the Democracy Index in West Java: The Importance to Strengthen the Accessibilities - Sahid, Asep Abdul; bin Shahruddin, Mohd. Solahuddin (Jurnal Politik Indonesia: Indonesian Political Science Review, 2018)
Political rights of citizen are an important aspect of Indonesian Democracy Index (IDI). However, in the 2014 Election, this aspect, particularly IDI of West Java, showed the lowest number. One of the efforts have been made by Election organizers to fulfill the political rights of citizen is to make accessibility as the principle of Election through Election Commission Regulation (PKPU). This study addresses why the aspect of the fulfillment of political rights of citizen is low in IDI; and how the principle of accessibility in to fulfill political rights of citizen is being implemented. The corpus of this study is document of IDI West Java Province and information of online media. The results indicate that; first, the implementation of the fulfillment of the political rights of citizen in the 2014 Election in West Java had a number of obstacles, namely the regulation of the accessibility principle is still limited; the lack of data of persons with disabilities; and the weakness of Election organizers concerning voters with disabilities. And secondly, efforts to implement the principle of accessibility by Election organizers are mostly concentrated in the election period implementation process, while the implementation process of the pre-election and post-election periods tends to be ignored.